Assessment of accessible facilities for disabled passenger movement in aerodrome terminals in Klang Valley - Ramli M.Z.; Hasnol J.N.E.; Hamid N.B.; Ismail N.; Zawawi M.H.; Zainal M.Z. (American Institute of Physics Inc., 2023)
The effectiveness of accessibility in public transport has prompted a great deal of weakness and confines many disabled from moving around unreservedly. As far as the built-up environment is concerned, it is important that it should be barrier-free and adapted to fulfill the needs of all people equally. The consideration of equal accessibility to outdoor environments is still lacking. These cause the problems with poor accessibility, the disabled people face more challenges and difficulties while travelling and using the public transport. Therefore, the aim of the study is to evaluate the performance of accessible facilities for disabled movement in aerodrome terminals in Klang Valley. An assessment rating was developed from an established guideline to assess the disabled facilities provided in the Aerodrome Terminal 1 and Aerodrome Terminal 2 by using manual observation and measurement technique. Based on the results obtained, the facility for disabled people in both aerodrome terminals are moderate. Aerodrome Terminal 1 is averagely 63.46% while for Aerodrome Terminal 2 is 67.31%. Results demonstrated that effort is needed by the respective agencies and there was a demand on re-designing the current facility, so that disabled people will not face any difficulty while traveling through public transport stations or terminals. 2017 Author(s).